EETIKA KERJA ISLAM SEBAGAI FAKTOR DETERMINAN TERHADAP KINERJA KARYAWAN PT. X DI KOTA BANDUNG - Widiansyah, Fauzan Akbar (Universitas Pendidikan Indonesia, 2019)
The main of this research is to resolve decreasing employee performance of Manufaturing Department at PT. X arround 3 years beginning of time, by using Islamic Work Ethics approach as independent variable. This research method used descriptive and verification method with 126 employees in the manufacturing department of PT. X as a population of with the number of respondents only 61 employees. The analysis technique used is Pearson product moment correlation coefficient and simple linear regression analysis. Then to test the research hypothesis, t-test is used to determine the significance level of the correlation coefficient between the two variables studied. The results showed that the Islamic Work Ethics and Employee Performance were in the middle category, and the calculation results of the correlation coefficient is 0.521, the mean is Islamic Work Ethic had a middle impact of Employee Performance.